2018
DOI: 10.1016/j.jhevol.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular bone patterning across the human hand

Abstract: Hand bone morphology is regularly used to link particular hominin species with behaviors relevant to cognitive/technological progress. Debates about the functional significance of differing hominin hand bone morphologies tend to rely on establishing phylogenetic relationships and/or inferring behavior from epigenetic variation arising from mechanical loading and adaptive bone modeling. Most research focuses on variation in cortical bone structure, but additional information about hand function may be provided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
60
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 33 publications
(73 citation statements)
references
References 246 publications
(1 reference statement)
8
60
0
Order By: Relevance
“…In contrast to these RBV/TV results, high DA throughout the human Mc1 head, while not overall significantly different from any species except gorillas, does not match our prediction of the highest DA at radiopalmar landmarks ( H1c ). Stephens et al () found slightly lower average DA values in a similar human Mc1 sample, likely due to their sampling of the whole distal epiphysis, but also found little regional differentiation across the Mc1 head in agreement with the results here. The present result may reflect the higher frequency of forceful prehensile thumb use in humans than in other extant hominids.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…In contrast to these RBV/TV results, high DA throughout the human Mc1 head, while not overall significantly different from any species except gorillas, does not match our prediction of the highest DA at radiopalmar landmarks ( H1c ). Stephens et al () found slightly lower average DA values in a similar human Mc1 sample, likely due to their sampling of the whole distal epiphysis, but also found little regional differentiation across the Mc1 head in agreement with the results here. The present result may reflect the higher frequency of forceful prehensile thumb use in humans than in other extant hominids.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, we predict flexion will be the dominant habitual movement in these grips, rather than adduction, reflected by the trabecular distribution in the nonhuman primate TMc joint (Figure b, bottom). In humans we predict RBV/TV and DA will be greater in the radiopalmar aspect of the Mc1 base ( H2c ; Figure a), due to habitual abduction and flexion during precision grasping (D'Agostino, Dourthe, Kerkhof, Stockmans, et al, ; Feix et al, ; Napier, ) as has been demonstrated before for RBV/TV (Stephens et al, ).…”
Section: Predictionssupporting
confidence: 68%
See 3 more Smart Citations